Disentangling the neural underpinnings of response inhibition in disruptive behavior and co-occurring ADHD - Saraçaydın, Gülhan; van Rooij, Daan; Kleine-Deters, Renee; Messchendorp, Marieke; Naaijen, Jilly; Penzol, María José; Rosa, Mireia; Aggensteiner, Pascal; Baumeister, Sarah; Holz, Nathalie E.; Banaschewski, Tobias; Saam, Melanie; et al. (European child & adolescent psychiatry, 2025)
While impaired response inhibition has been reported in attention-deficit/hyperactivity disorder (ADHD), findings in disruptive behavior disorders (DBDs) have been inconsistent, probably due to unaccounted effects of co-occurring ADHD in DBD. This study investigated the associations of behavioral and neural correlates of response inhibition with DBD and ADHD symptom severity, covarying for each other in a dimensional approach. Functional magnetic resonance imaging data were available for 35 children and adolescents with DBDs (8-18 years old, 19 males), and 31 age-matched unaffected controls (18 males) while performing a performance-adjusted stop-signal task. No significant association was found between behavioral performance and symptom severities. However, contrasting successful inhibition with failed inhibition revealed that DBD and ADHD symptom severity was associated with greater activation in the right inferior frontal regions and reduced activation in the bilateral striatal regions, respectively. During successful inhibition versus go-trials, ADHD symptom severity was associated with the left lateral occipital cortex activation. The contrast of failed inhibition versus go-trials revealed reduced activation in the right frontal and left parietal regions associated with DBD symptom severity while ADHD symptom severity was associated with bilateral precunei, dorsolateral prefrontal and left posterior parietal regions. Except for the right inferior frontal regions during successful versus failed inhibition, all clusters were also found to be inversely associated with the other dimension of interest (i.e., DBD or ADHD symptoms). Opposite direction of the associations between DBD and ADHD symptom severity, and fronto-parietal and fronto-striatal activation suggest unique contributions of DBD and ADHD to the neural correlates of response inhibition.